Pengaruh Atmosfer Cafe dan Gaya Hidup Terhadap Keputusan Pembelian Konsumen di Cafe at Back Coffee Pangkalpinang - Juwita, Juwita; Sabila, Enggel Dwi; Noviyanti, Indah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
The development of the coffee industry in Indonesia shows significant growth, with coffee shops no longer just a place to enjoy drinks, but also a social space for the younger generation. This study analyzes the influence of cafe atmosphere and lifestyle on consumer purchasing decisions at Cafe at Back Coffee Pangkalpinang, focusing on the younger generation aged 15-40 years. Using a quantitative explanatory approach method and purposive sampling technique, the study involved 150 respondents who were studied through questionnaires and observations, and analyzed using SmartPLS 4. The results showed that cafe atmosphere and lifestyle had a positive and significant effect on consumer purchasing decisions, with the ability to explain 62.7% of the variation in purchasing decisions. The findings revealed that elements such as interior design, lighting, music, aroma, and cafe service quality, as well as the dynamic lifestyle of the younger generation substantially influence consumer preferences. The study provides theoretical contributions in understanding consumer behavior in the coffee shop industry and practical implications for cafe managers to develop marketing strategies that focus on consumer experience and contemporary lifestyle trends.